RELATIONSHIP BRAND CHARACTERISTICS, COMPANY CHARACTERISTICS AND CONSUME R-BRAND CHARACTERISTICS WITH BRAND LOYALTY (CASE STUDY OF SARIMI CONSUMERS IN SAMARINDA) - Yoshua Pandapotan Siringoringo; Muhammad Jacky Murdani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study is to determine the relationship between brand characteristics, company characteristics and consumer-brand characteristics with brand loyalty to Sarimi customers in Samarinda. The technique of collecting data in this study was by collecting a questioner. The types of data used in this study are primary and secondary data. The number of samples in this study were 100 people who are Sarimi consumers. Data obtained using the validity and reliability test, as well as the Spearman trial with the SPS S program. Brand Characteristics, Company Characteristics and Consumer-Brand Characteristics have a significant and strong relationship with Brand Loyalty.